Phase relationships in the Al-rich region of the Al-Y-Zr system - Bao, Xiaoheng; Liu, Libin; Huang, Shuaixiong; Jiang, Yun; Wang, Xing; Zhang, Ligang (Journal of Mining and Metallurgy, Section B: Metallurgy, 2016)
The phase relations in the Al-Y-Zr ternary system at 873 K have been investigated by X-ray powder diffraction (XRD) and scanning electron microscope (SEM) with energy disperse X-ray spectroscopy (EDS) in backscattered electron imaging (BSE) modes. Six three-phase equilibria were determined and no ternary compound was observed.